Sistema informático con tecnología electrónica para mejorar el proceso de regadío agrícola en las zonas desérticas de la provincia del Carchi - Castillo Montenegro, William Fernando (2019)
The development of technology is revolutionizing the world as it has made it easier to perform daily tasks. Thus, the study and development of applications for human wellbeing is constantly evolving, so in this research work has been proposed the development of an application to improve the irrigation process in desert areas of the Province of Carchi in order to take advantage of land in which it is practically impossible to carry out agriculture. This technology will provide an automatic opening of water pumps according to the humidity of the land; that is, if the land becomes dry, the system automatically takes care of irrigating until the humidity level is optimal for the growth of plants. This type of technology offers a number of options both economically and technologically, since this type of devices streamline the irrigation of desert lands. Through the development of this research work, the proposed objectives are achieved which allow a reduction in costs and ease in the irrigation process. Regarding, the technical part, the main objective is to propose the development and proper functioning of the computer system for irrigation, thus improving the quality of life of people living in desert areas in the Province of Carchi.